A Review of Quinazoline-Based EGFR/VEGFR-2 Dual Inhibitors as Potent Anticancer Agents: Structure-Activity Relationship and Docking Studies - Fatemeh Yousefbeyk; Saeed Ghasemi (Pharmaceutical Sciences)
The epidermal growth factor receptor (EGFR) is a receptor tyrosine kinase (RTK) that initiates various signaling pathways resulting in processes such as gene expression, proliferation, angiogenesis, and inhibition of apoptosis. Dysregulation of EGFR signaling causes tumor development and metastasis. Therefore, targeting EGFR can be introduced as a promising way for cancer treatment. Angiogenesis, the formation and growth of new capillaries from pre-existing vasculature, is a key process in many physiological and pathological processes, including embryonic development, tissue growth, wound healing, cancer, rheumatoid arthritis, diabetic retinopathy, axon growth, and inflammatory diseases. Vascular endothelial growth factor receptors (VEGFRs), as receptor tyrosine kinases, especially VEGFR-2, have been introduced as the main mediators of angiogenesis. Therefore, VEGFR-2 inhibitors could be attractive agents for blocking angiogenesis and tumor growth. Due to the common downstream signaling pathways of EGFR and VEGFR-2, simultaneous inhibition of both receptor tyrosine kinases can be used as a valuable method in cancer therapy. Targeting the ATP-binding site of the tyrosine kinase domain using small molecules, either reversibly or irreversibly, is one way to inhibit EGFR and VEGFR-2. Different drugs with various scaffolds such as quinazoline (Vandetanib) and pyrimidine (Regorafenib) have been approved by the FDA for the treatment of various malignancies. Among them, the quinazoline skeleton is an attractive core with a wide range of activities. Vandetanib, a quinazoline-based EGFR/VEGFR-2 dual inhibitor, is an orally administered drug for the treatment of locally advanced or metastatic medullary thyroid cancer. Due to the limited number of multitarget kinases, as well as limitations in their clinical efficacy, adverse effects, and drug resistance, there is a vital need to introduce novel inhibitors with superior selectivity and efficacy compared to existing ones to overcome these challenges. Therefore, we reviewed the structure-activity relationship (SAR), EGFR/VEGFR-2 inhibitory activities, anticancer effects, and docking studies of synthesized quinazoline-based EGFR/VEGFR-2 dual inhibitors.